2014
DOI: 10.1002/lary.25064
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of epilepsy by stimulation of the vagus nerve from Head‐and‐Neck surgical point of view

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The complication rate of this study corresponds to previous literature that showed surgical complication rates ranging from 4.2 to 16.7%. ( Lotan and Vaiman, 2015 ; Révész and Ben-Menachem, 2016 ; Kahlow and Olivecrona, 2013 ; Spindler et al, 2021 ). In total, three permanent complications occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complication rate of this study corresponds to previous literature that showed surgical complication rates ranging from 4.2 to 16.7%. ( Lotan and Vaiman, 2015 ; Révész and Ben-Menachem, 2016 ; Kahlow and Olivecrona, 2013 ; Spindler et al, 2021 ). In total, three permanent complications occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates range between 4.2 and 16.7%, depending on the exact definition of a surgical complication and the type of VNS surgery evaluated (primary implantation, pulse generator replacement, lead replacement, or removal surgery) ( Lotan and Vaiman, 2015 ; Révész and Ben-Menachem, 2016 ; Kahlow and Olivecrona, 2013 ; Spindler et al, 2021 ). Well-known risk factors for getting surgical complications in general include smoking, obesity, diabetes, duration of surgery, use of immunosuppressive medication, and length of preoperative hospitalization ( Anderson, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Side effects of neurostimulation can include coughing, hiccups, dysphagia, and hoarseness associated with stimulation of the retrobulbar laryngeal nerve. After implantation of a vagus nerve stimulator, periodic monitoring and programming of the ruler is necessary [17,18,19,20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Positioning the electrode on the right side would be associated with a higher risk of arrhythmia due to the effect of the right vagus nerve on the atrial-ventricular node of the stimulus-conducting system of the heart [73][74]. Stimulation is associated with potential side effects, among which can be distinguished cough, hiccups, dysphagia, and hoarseness associated with excitation of the posterior laryngeal nerve [75].…”
Section: Ethosuximidementioning
confidence: 99%